Model of conflict interaction objects cyberspace - Семко, В. В. (Problems of Informatization and Control, 2012)
The methods of formal description of the conflict interaction objects information and telecommunication systems in cyberspace as a subspace information space. Synthesized model of conflict interaction of virtual objects. The method of integral truncation options as an approach to solving the problem of prevention and resolution of conflicts interaction of cyberspace